Fenomena Mahasiswa Generasi Z Di Instagram (Studi Kualitatif Fenomenologi Mengenai Motif Di Balik Kosongnya Feed Instagram Pada Mahasiswa Ilmu Komunikasi, Universitas Dharma Andalas) - Fachry Akbar (CV. ITTC INDONESIA, 2026)
This study aims to understand the motives of Communication Science students at Dharma Andalas University for emptying their Instagram feeds. This phenomenon, known as